Mind, Body, Motion, Matter Eighteenth-Century British and French Literary Perspectives - McMurran, Mary Helen; Conway, Alison (University of Toronto Press, 2016)
Mind, Body, Motion, Matter investigates the relationship between the eighteenth century's two predominant approaches to the natural world- mechanistic materialism and vitalism- in the works of leading British and French writers such as Daniel Defoe, William Hogarth, Laurence Sterne, the third Earl of Shaftesbury and Denis Diderot. Focusing on embodied experience and the materialization of thought in poetry, novels, art, and religion, the literary scholars in this collection offer new and intriguing readings of these canonical authors. Informed by contemporary currents such as new materialism, cognitive studies, media theory, and post-secularism, their essays demonstrate the volatility of the core ideas opened up by materialism and the possibilities of an aesthetic vitalism of form.This title was made Open Access by libraries from around the world through Knowledge Unlatched.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: History; History; Electronic books